TOOLS FOR DEVELOPING MATHEMATICAL LITERACY SKILLS IN PRIMARY CLASS STUDENTS - Dilbar DAMINOVA (Scholar Express Journal, 2024)
The article focuses on the formation and development of the system of mathematical knowledge and skills necessary for mathematical literacy in elementary school students. The essence of mathematical literacy as an activity is revealed, such as conducting mathematical reasoning, applying mathematical concepts, methods, facts and tools
Keywords: mathematics; reasoning; problem solving